EDITORIAL PREFACE (Volume 7, Issue 2, November 2019) - Pangaribuan, Christian Haposan (Journal of Business And Entrepreneurship, 2019)
Journal of Business and Entrepreneurship, Volume 7, Issue 2, November 2019.